Influence of passive smoking on learning in elementary school - Juliana Gomes Jorge; Clóvis Botelho; Ageo Mário Cândido Silva; Gisele Pedroso Moi (Elsevier, 2016)
Abstract Objective To analyze the association between household smoking and the development of learning in elementary schoolchildren. Methods Cross-sectional study with 785 students from the 2nd to the 5th year of elementary school. Students were evaluated by the School Literacy Screening Protocol to identify the presence of learning disabilities. Mothers/guardians were interviewed at home through a validated questionnaire. Descriptive and bivariate analysis, as well as multivariate Poisson regression, were performed. Results In the final model, the variables associated with learning difficulties were current smoking at the household in the presence of the child (PR = 6.10, 95% CI: 4.56 to 8.16), maternal passive smoking during pregnancy (PR = 1.46, 95% CI: 1.07 to 2.01), students attending the 2nd and 3rd years of Elementary School (PR = 1.44, 95% CI: 1.10 to 1.90), and being children of mothers with only elementary level education (PR = 1.36, 95% CI: 1.04 to 1.79). Conclusion The study demonstrated an association between passive exposure to tobacco smoke and learning difficulties at school.